INA's experience of cooperation in Portuguese-speaking African countries: How to bridge the gap between training and cooperation and climate governance? - Nave, A.; Asensio, M. (1st International UNITAR Research Conference: "CLIMATE SECURITY: PEACE & SECURITY CONSEQUENCES OF CLIMATE CHANGE", 24th November, 2023)
This article aims to explore Portugal’s cooperation agenda in Portuguese-speaking African countries over the past two decades. The focus is on understanding Portuguese's efforts to bridge the gap between the training and cooperation agenda in a rapidly evolving governance landscape that emphasises the threats and risks that stem from climate change and affect peace and security prospects. As will be analyzed, climate security and related risks have implications that profoundly influence governance, conflict, and peace (Anne Mette Kjær 2014; Sriram 2008; Leftwich 1993; Behn 2001; UNDP 2002; Brinkerhoff 2006; Grindle 2010). This article examines these countries' relations with Portugal and the political, economic, social and diplomatic trajectories they have followed in order to explore how we understand international order and global stability in the face of this tension between climate change, security and development. Firstly, it aims to acquire knowledge to understand the impact that climate change can have on governance. Secondly, how can we properly assess the challenges around this tension and this growing relationship. Finally, we will examine the different training and cooperation programs that have been developed in PALOP. By identifying lessons learnt from the National Institute for Administration's (INA) experience in the areas of training and cooperation, this paper aims to share valuable information and also to pose questions that will be of interest for future research and studies in the field of governance consequences of climate change.